Prevalence of drug-drug interactions for oral anticoagulant drugs in patients with atrial fibrillation and relationship with outcomes: a population-based cohort study. (25th November 2020) - Proietti, M; Cortesi, L; Spagnoli, F; Nobili, A; Marengoni, A
Abstract: Introduction: The introduction of non-vitamin K antagonist oral anticoagulants (NOACs) changed the treatment of atrial fibrillation (AF) patients, promising a better safety profile and a lower chance of interaction with drugs than vitamin K antagoniste (VKA). Aim: To evaluate the prevalence of possible drug-drug interactions (DDIs) in a cohort of newly anticoagulated AF patients, their impact on outcomes and possible differences between VKA and NOACs users. Methods: We performed an analysis derived from administrative databases in Lombardy Italian region. All patients ≥40 years admitted from 01/06/2013 to 30/06/2018 with an AF diagnosis that were VKA or NOACs new users were included in this analysis. Possible DDIs were evaluated according to the prescription of OAC therapy, on the basis of current available evidence. Stroke, intracerebral hemorrhage (ICH), any bleeding and all-cause death were the study outcomes. Results: Among the 122816 patients included in the analysis, mean (SD) age 76.3 (9.6) with 47.3% females, a mean (SD) CHA2DS2-VASc of 3.5 (1.4) was found. A total of 70180 (57.1%) patients were prescribed with VKA and 52636 (42.9%) with NOACs. A possible DDI was recorded in 63273 (51.5%). Patients exposed to DDIs were older and less likely female (both p<0.0001) and with a higher mean (SD) CHA2DS2-VASc (p<0.0001). Rate of stroke, ICH, any bleeding and all-cause death were higher in those patients exposed to DDIs (all p<0.001). After full adjustment, exposure to possible DDIs was associated with an increased risk for any bleeding (HR: 1.08, 95% CI: 1.05–1.12) and all-cause death (HR: 1.10, 95% CI: 1.07–1.13), with no differences for stroke and ICH. Comparing VKA and NOACs patients exposed to possible DDIs, we found that VKA users exposed to possible DDIs, after adjustments, were at higher risk for all the outcomes (Table). Conclusions: In a large cohort of AF patients newly prescribed with OAC, possible DDIs were largely prevalent, in particular in VKA users. Presence of a possible DDI is associated with an increased risk of any bleeding and all-cause death. VKA users exposed to a possible DDI were at higher risk for any outcome than NOACs users exposed to a possible DDI. Funding Acknowledgement: Type of funding source: None